Assessment of Disease Resistance and High Yielding Traits of Common Buckwheat Genotypes in Subtropical Climate of Nepal (SAARC Journal of Agriculture, 2020)
Twelve common buckwheat (Fagopyrum esculentum Moench) genotypes received from Hill Crops Research Program, Kabre, Dolakha were evaluated for resistance against major foliar fungal diseases and high yielding traits at the research field of National Maize Research Program, Rampur, Chitwan during winter seasons of two consecutive years 2017 and 2018. The design of the experiment was Randomized Complete Block having three replications. The unit plot size was 3m x 2m with 25cm row to row spacing and continues plant to plant spacing was maintained and net harvested plot was 6 sq meters. The experiment was planted at last week of October in both years. The recommended dose of fertilizer was 30:30:0 for N:P:K kg ha-1 respectively and seed rate 50 kg ha-1. Disease data were recorded for downy mildew (Perenospora fagopyri), powdery mildew (Erysiphepolygoni) and botrytis leaf blight (Botrytis cinerea) severity on 20 randomly tagged plants/plot. The yield and yield attributing traits were recorded. Buckwheat genotypes differed significantly (p